Abnormality Detection in Kidney Ultrasound Imaging (International Journal of Engineering and Computer Science, 2018)
This paper proposes a technique for segmentation and identification of kidney stone from the ultrasound image of kidney. Initially ultrasound kidney image is pre-processed using two types of filters namely median filter and wavelet filter. Pre-processed image is taken as input for segmentation process; seed region growing algorithm is used to segment the renal calculi from ultrasound image of kidney, further region parameters are extracted from the segmented region. Finally area of each renal calculi and time taken for the entire process is calculated.